2021
DOI: 10.1002/cyto.a.24464
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of chromatin proteins to nucleoli—The influence of protein dynamics on post‐fixation localization

Abstract: It is expected that the subnuclear localization of a protein in a fixed cell, detected by microscopy, reflects its position in the living cell. We demonstrate, however, that some dynamic nuclear proteins can change their localization upon fixation by either crosslinking or non-crosslinking methods. We examined the subnuclear localization of the chromatin architectural protein HMGB1, linker histone H1, and core histone H2B in cells fixed by formaldehyde, glutaraldehyde, glyoxal, ethanol, or zinc salts. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…We also successfully simulated the bifurcating fixation artifacts on LLPS systems that were observed experimentally and showed that both LLPS-enhancing and diminishing effects are possible depending on the relative fixation rates of the protein in and out of its puncta . Predictions based on our model are consistent with experimental observations that more dynamic protein-binding events are more poorly preserved by fixation and further suggest that the severity of fixation artifacts is dependent on the overall rates of fixation relative to protein binding, rather than protein binding and unbinding rates themselves. This is consistent with the observation that while PFA artificially evicts Esrrb from mitotic chromatin, glyoxal, a cross-linker with a faster fixation rate than PFA, faithfully preserves this mitotic binding activity. ,, Furthermore, our model explains PFA/FA fixation-induced depletion of TFs from mitotic chromatin as that the fixation rate of TF molecules bound to chromatin is slower than that of unbound molecules, which is consistent with the explanation using the cross-linking gradient model.…”
Section: Fixation Quality Can Be Related To Protein Binding Dynamicssupporting
confidence: 67%
See 2 more Smart Citations
“…We also successfully simulated the bifurcating fixation artifacts on LLPS systems that were observed experimentally and showed that both LLPS-enhancing and diminishing effects are possible depending on the relative fixation rates of the protein in and out of its puncta . Predictions based on our model are consistent with experimental observations that more dynamic protein-binding events are more poorly preserved by fixation and further suggest that the severity of fixation artifacts is dependent on the overall rates of fixation relative to protein binding, rather than protein binding and unbinding rates themselves. This is consistent with the observation that while PFA artificially evicts Esrrb from mitotic chromatin, glyoxal, a cross-linker with a faster fixation rate than PFA, faithfully preserves this mitotic binding activity. ,, Furthermore, our model explains PFA/FA fixation-induced depletion of TFs from mitotic chromatin as that the fixation rate of TF molecules bound to chromatin is slower than that of unbound molecules, which is consistent with the explanation using the cross-linking gradient model.…”
Section: Fixation Quality Can Be Related To Protein Binding Dynamicssupporting
confidence: 67%
“…They found that only the wild-type and mutants with chromatin-binding residence half-times longer than 5 s as measured by FRAP were well-preserved by 4% PFA fixation . Consistently, it has been shown that many stable chromatin-binding proteins are well preserved by fixation, including the histone protein H2B, , TATA-binding protein (TBP), and CCCTC-binding factor (CTCF). , In contrast, Sox2, which more transiently binds to mitotic chromatin than H2B according to FRAP and single-particle tracking (SPT) measurements, is artificially released to the nucleoplasm upon fixation with PFA . These findings collectively suggest that proteins that bind to chromatin with longer residence times are better preserved by fixation.…”
Section: Fixation Quality Can Be Related To Protein Binding Dynamicsmentioning
confidence: 89%
See 1 more Smart Citation
“…A classic example of experimental evidence for the nucleolar localization of an otherwise nuclear protein LEO1 (RNA polymerase- associated protein), was previously obtained using a GFP-labelled cell line 83, 122, 123 . In addition, GFP- tagged chromatin architecture protein HMGB1 (High Mobility Group Protein B 1, a nonhistone nucleoprotein and an extracellular inflammatory cytokine) was shown to localize to the nucleoplasm in live imaging but to nucleoli after FA fixation 124 . However, hiPSC NR2F1-GFP always showed exclusively nucleoplasmic but not nucleolar localization, as demonstrated by live imaging and confirmed by staining with two different AbGFP after FA fixation.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that because our four-state model makes no assumptions about any state being phase-separated, the logical implications of our model can extend beyond LLPS to other biomolecular transactions and cellular structures that have been found not well preserved by fixation or immunofluorescence, including localizations of cilia proteins (Hua and Ferland, 2017), clustering of cell membrane receptors (Stanly et al, 2016), splicing speckle formation (Neugebauer and Roth, 1997), and chromatin organization and protein binding (Zarębski et al, 2021; Lorber and Volk, 2022; Lerner et al, 2016; Pallier et al, 2003; Kumar et al, 2007; and Teves et al, 2016). Our model can similarly extend beyond PFA to other fixatives.…”
Section: Discussionmentioning
confidence: 99%